The synthesis of ph-responsıve polymeric film wıth an enhanced mechanical properties for wound dress applications - Evranos, Begüm (My University, 2019)
İyileştirilmiş mekanik performansa sahip polimerik filmler, çeşitli konsantrasyonlarda (% 0-25) kemik tozunun kitosan/ jelatin (CTS / GEL) polimerik yapısına eklenmesi ile yara iyileştirici bir pansuman malzemesi olarak üretilmiştir. Elde edilen filmlerin karakterizasyonu FT-IR, XRD ve SEM analizleri ile gerçekleştirilmiştir. Polimerik filmlerin mekanik performansı, mekanik test cihazı ile belirlenmiştir. Yapılan mekanik test sonuçları, kemik tozunun polimerik filmlerin yapısına katılmasının, polimerik filmlerin elastik modülünü ve gerilme kuvvetini önemli ölçüde arttırdığını kanıtlamıştır. Kemik tozu takviyesi ile polimerik filmlerin oksijen geçirgenliği ve su buharı geçirgenlik hızı da iyileştirilmiştir. Film numunelerinin su tutma kapasitesini ve pH’a duyarlılığını değerlendirmek için farklı pH değerlikli tampon çözeltilerinde (5.8 ve 7.4) şişme testi yapılmıştır. Biyouyumluluğun belirlenmesi için sitotoksisite testi yapılmıştır. Antibakteriyel model ilaç olarak siprofloksasin seçilmiştir. Polimerik filmlere kemik tozunun eklenmesi sayesinde siprofloksasin salımının pH 7.4'te, daha kontrollü bir şekilde sağlandığı görülmüştür. Ayrıca, antibakteriyel ilaç yüklenmiş filmler Escherichia coli ve Bacillus subtilis bakterilerine karşı mükemmel antibakteriyel aktivite göstermiştir. Sonuçlar siprofloksasin yüklenmesi yapılmış, kemik tozu ile güçlendirilmiş kitosan/ jelatin kompozit filmlerin, kontrollü ilaç salımı uygulanmalarında yara örtüsü olarak uygulanabilir potansiyele sahip olduğunu kanıtlamaktadır.

Polymeric films with enhanced mechanical performance were fabricated by incorporation of bone ash (BA) at various concentrations (0 to 25 v. %) into chitosan/ gelatin (CTS/ GEL) polymeric structure as a wound healing-dressing. The obtained films were characterized by FT-IR, XRD and SEM techniques. Mechanical performance of polymeric films was determined by a universal mechanical tester. The results for mechanical performance of polymeric films proved that the encapsulation of BA into the polymeric films enhances the elastic modulus and tensile strength of polymeric films significantly. Oxygen permeability and water vapor transmission rate of films were also improved by bone ash reinforcement. Swelling test was carried out at the buffer solutions with different pH values (5.8 and 7.4) to evaluate the water uptake capacity and to confirm the pH responsivity of the film samples. Cytotoxicity test was performed to determine biocompatibility. Ciprofloxacin was chosen as the antibacterial model drug. The release of ciprofloxacin was provided in a more controlled manner at pH 7.4 owing to the incorporation of bone ash into the polymeric films. Also, drug loaded films showed great antibacterial activity against Escherichia coli and Bacillus subtilis bacteria. The results prove that ciprofloxacin loaded BA reinforced chitosan/ gelatin composite films are potentially applicable in controlled drug delivery as wound dressings.
Keywords: bone ash; Chemical engineering; ciprofloxacin; gelatin; jelatin; kemik tozu; Kimya mühendisliği; Kitosan; mechanical performance; mekanik performans; siprofloksasin Chitosan; wound dressing; yara örtüsü